The Factors Influencing Impulsive Buying Behavior In Live Streaming Shopping Based On S-O-R Model - Peng, Wensi (2025)
Live streaming shopping is rapidly emerging. Especially in China, its market size reached approximately 3.5 trillion CNY in 2022. In light of this background, this study examines how live streaming shopping influences consumers’ impulsive buying behavior. By applying the Stimulus–Organism–Response (S-O-R) model, it investigates how streamer information source characteristics (streamer attractiveness, expertise, and interaction) and promotional urgency cues (perceived pricing tactics and perceived time scarcity) shape consumers’ hedonic and utilitarian value perceptions, which in turn drive impulsive buying behavior. A quantitative survey was conducted on Wenjuanxing, a major Chinese online platform for survey creation and distribution similar to SurveyMonkey, involving 313 Chinese consumers who regularly engage with live streaming shopping, specifically those who have watched Dong Yuhui’s Douyin sessions. After data cleaning, 301 valid responses were retained for analysis (N = 301). Structural equation modeling (SEM) was employed to validate the conceptual model and test hypotheses concerning both direct and mediating effects. Data analysis was performed using IBM SPSS 27 and IBM SPSS Amos 26. Key findings show that streamer attractiveness, expertise, and interaction all significantly enhance hedonic value, while perceived pricing tactics boost both hedonic and utilitarian values. By contrast, neither streamer interaction nor perceived time scarcity significantly affect utilitarian value. Additionally, both hedonic and utilitarian values serve as important mediators between live streaming stimuli and impulsive buying behavior. By extending the S-O-R framework to the live streaming shopping context, this study expands the model’s applicability. Specifically, this study not only advances theoretical understanding in live streaming shopping context but also offers practical insights for business and platforms operators seeking to boost consumer engagement and optimize sales strategies in live streaming shopping context.